2016
DOI: 10.1073/pnas.1601002113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic periplasmic chaperone reservoir facilitates biogenesis of outer membrane proteins

Abstract: Outer membrane protein (OMP) biogenesis is critical to bacterial physiology because the cellular envelope is vital to bacterial pathogenesis and antibiotic resistance. The process of OMP biogenesis has been studied in vivo, and each of its components has been studied in isolation in vitro. This work integrates parameters and observations from both in vivo and in vitro experiments into a holistic computational model termed "Outer Membrane Protein Biogenesis Model" (OMPBioM). We use OMPBioM to assess OMP biogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 53 publications
9
65
0
Order By: Relevance
“…The insertion of OmpF into a bilayer with the periplasmic turns first is not observed in the bacterialO M, where assemblyo ft he porin is guided by chaperonesa nd the b-barrel assembly machinery. [36,37] In PLBs, maltoporin (another trimeric E. coli OM protein) hasbeen observed to insert predominantly with the periplasmic side first from diluted octyl-POE at an applied potential of AE (100-200 mV). [28] Our reconstitution protocol similarly uses potentials in the AE (200-300) mV range to insert OmpF from diluted bOG, and it is unclear why we saw both orientationswith equal probability.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of OmpF into a bilayer with the periplasmic turns first is not observed in the bacterialO M, where assemblyo ft he porin is guided by chaperonesa nd the b-barrel assembly machinery. [36,37] In PLBs, maltoporin (another trimeric E. coli OM protein) hasbeen observed to insert predominantly with the periplasmic side first from diluted octyl-POE at an applied potential of AE (100-200 mV). [28] Our reconstitution protocol similarly uses potentials in the AE (200-300) mV range to insert OmpF from diluted bOG, and it is unclear why we saw both orientationswith equal probability.…”
Section: Discussionmentioning
confidence: 99%
“…While chaperones ensure that nascent OMP chains transit across the aqueous periplasm, insertion into the outer membranes is the final, rate-limiting step in OMP maturation. 58 This reaction is catalyzed by the multi-protein BAM complex in which the central essential subunit, BamA, is itself a transmembrane β-barrel. By its very nature, BamA must have extensive interactions with membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction rate of Skp binding OmpC is nearly diffusion limited 30 . The association rate constant could be estimated by…”
Section: Discussionmentioning
confidence: 99%
“…When OMP polypeptide was synthesized by ribosome in the cytoplasm, the polypeptide would be secreted to periplasm through SecYEG/SecA translocon in unfolded state and safeguarded by chaperones including Skp3 1,26-29 . Many articles showed that OMP×Skp3 has a dissociation constant of nano-molar range19,30,31 . Most their experiments, however, were performed at ensemble level of OMPs,…”
mentioning
confidence: 99%